Teachers' Efforts in Developing Social Emotional Kindergarten Students - Ramadan, Syahru; Adriani, Adriani (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2023)
Social-emotional is one of the important aspects developed in children from an early age. This is because social-emotional development will have an impact on the further development of children. This development can begin in early childhood education in the age range of 5-6 years. The purpose of this study is to explore teacher efforts for developing social-emotional students. This research is in the form of qualitative descriptive research using data collection techniques in the form of observation and interviews at Al-Mubarak Kindergarten and Ash-Shiddiq IT Kindergarten, Bone Regency. The data collected is then processed with three stages of analysis, namely data reduction, data display, and verification or conclusion. The results of this study found that there are several efforts used by teachers to develop social-emotional students, including rapport, positive reinforcement, and matching and mirroring in aspects of self-awareness, advice and appreciation in the form of positive affirmations in aspects of responsible attitudes, and direct direction and practical learning in aspects prosocial behavior. These efforts can be modeled and developed again by parents and other teachers.